Pengaruh Electronic Service Quality, System Quality, Dan Customer Trust Terhadap Repurchase Intention - Zahirah, Anissa; Puspaningrum , Astrid (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The increasing number of businesses has created competition among e-commerce companies. Lazada is one of the largest e-commerce in Indonesia, which has experienced a decline in visitors and received a lot of criticism through social media. This phenomenon indicates a decrease in the repurchase intention of Lazada consumers in Indonesia. This study aims to examine and explain the effect of electronic service quality, system quality, and customer trust on repurchase intention in Lazada e-commerce in Malang City. This type of the research is explanatory research which explains the position and relation between the variables studied through hypothesis testing. This research involved 140 respondents who had made purchases at Lazada e-commerce in Malang City. Sampling used a non-probability sampling technique with a purposive sampling method with the characteristics of domiciled in Malang City and having made a purchase through Lazada e-commerce at least once. This study used SPSS 29 to perform multiple linear regression tests. The results of this study indicate that electronic service quality has a significant effect on repurchase intention, system quality has a significant effect on repurchase intention, and customer trust has a significant effect on repurchase intention in Lazada e-commerce. Abstrak Meningkatnya jumlah pelaku bisnis telah menciptakan persaingan di antara perusahaan e-commerce. Lazada merupakan salah satu e-commerce terbesar di Indonesia yang mengalami penurunan pengunjung dan mendapatkan banyak kritikan melalui media sosial. Fenomena ini menunjukkan adanya penurunan pembelian berulang (repurchase intention) konsumen Lazada di Indonesia. Penelitian ini bertujuan untuk menguji dan menjelaskan pengaruh electronic service quality, system quality, dan customer trust terhadap repurchase intention pada e-commerce Lazada di Kota Malang. Jenis penelitian ini adalah penelitian eksplanatori (explanatory research) yang menjelaskan kedudukan dan hubungan antara variabel-variabel yang diteliti melalui pengujian hipotesis. Penelitian ini melibatkan 140 responden yang pernah melakukan pembelian pada e-commerce Lazada di Kota Malang. Pengambilan sampel menggunakan teknik non-probability sampling dengan metode purposive sampling dengan karakteristik berdomisili di Kota Malang dan pernah melakukan pembelian melalui e-commerce Lazada minimal satu kali. Penelitian ini menggunakan SPSS 29 dengan melakukan uji regresi linear berganda. Hasil penelitian ini menunjukkan bahwa electronic service quality berpengaruh signifikan terhadap repurchase intention, system quality berpengaruh signifikan terhadap repurchase intention, dan customer trust berpengaruh signifikan terhadap repurchase intention di e-commerce Lazada.